(untitled) (Bangladesh Journal of Plant Taxonomy, 2008)
The heliconias, now widely grown in Bangladesh as ornamental plants, have been classified into eight species with four cultivars, and two hydrids. Dichotomous bracketed keys to the taxa, detailed taxonomic descriptions with colour photographs, time of flowering and distribution have been provided. English names and chromosome numbers have also been furnished wherever available. Â Keywords: Heliconia, Cultivated, Keys and descriptions, Bangladesh Â DOI: 10.3329/bjpt.v15i2.1752 Â Bangladesh J. Plant Taxon. 15(2): 141-153, 2008 (December)